2019
DOI: 10.1002/jmd2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the serum metabolome of patients with alkaptonuria before and after two years of treatment with nitisinone using LC‐QTOF‐MS

Abstract: Background The homogentisic acid‐lowering therapy nitisinone is being evaluated for the treatment of alkaptonuria (AKU) at the National Centre for AKU. Beyond hypertyrosinemia, the wider metabolic consequences of its use are largely unknown. The aim of this work was to evaluate the impact of nitisinone on the serum metabolome of patients with AKU after 12 and 24 months of treatment. Methods Deproteinized serum from 25 patients with AKU (mean age[±SD] 51.1 ± 14.9 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
5
19
1
Order By: Relevance
“…The increases in tyrosine metabolites, excluding HGA, were unexpected in untreated AKU. Increases in metabolites upstream of HPPD previously reported in nitisinonetreated AKU were thought to be a direct consequence of the inhibition of HPPD by nitisinone and the consequential hypertyrosinaemia (Davison et al, 2019a;. For the first time, the present data show that targeted Hgd disruption in Hgd -/mice induces metabolic changes upstream of HGA, despite no increase in tyrosine, HPPA or HPLA.…”
Section: Alteration To Tyrosine Metabolismsupporting
confidence: 73%
See 4 more Smart Citations
“…The increases in tyrosine metabolites, excluding HGA, were unexpected in untreated AKU. Increases in metabolites upstream of HPPD previously reported in nitisinonetreated AKU were thought to be a direct consequence of the inhibition of HPPD by nitisinone and the consequential hypertyrosinaemia (Davison et al, 2019a;. For the first time, the present data show that targeted Hgd disruption in Hgd -/mice induces metabolic changes upstream of HGA, despite no increase in tyrosine, HPPA or HPLA.…”
Section: Alteration To Tyrosine Metabolismsupporting
confidence: 73%
“…Nitisinone reduces plasma and urine HGA concentrations (Phornphutkul et al, 2002;Introne et al, 2011;Olsson et al, 2015;Ranganath et al, 2016;Milan et al, 2017), completely arrests ochronosis in AKU mice (Preston et al, 2014;Keenan et al, 2015) and more recently was shown to slow progression of morbidity in patients attending the UK NAC (2mg nitisinone daily) (Ranganath et al, 2018). We showed previously in serum and urine that nitisinone induced an extended network of metabolic alteration within tyrosine and neighbouring pathways, including tryptophan, purine and TCA cycle (Davison et al, 2019a;Norman et al, 2019). This alteration is a concern in AKU, and particularly in hereditary tyrosinaemia type-1, another inherited disorder of tyrosine metabolism, in which nitisinone treatment is essential from early infancy (McKiernan et al, 2015).…”
Section: Associated Alteration To Tyrosine Purine and Tca Cycle Metamentioning
confidence: 92%
See 3 more Smart Citations